Demystifying archival projects five essentials for success - Note, Margot
"Demystifying Archival Projects: Five Essentials for Success will benefit archivists who lead or participate in projects without formal project management training. As work in archives continues to become more project-driven, educational and professional development opportunities for archivists have not kept pace. This book aims to provide the needed information--just enough project management methodology--to bridge that knowledge gap."--Back cover